COVID-19 What do people hospitalised with COVID-19 think about their care? Results of a satisfaction survey during the first wave of COVID-19 in Liverpool. Issue 1 (2021) - Wu, Meng-San; Watson, Rebecca; Hayat, Fatima; Ratcliffe, Libuse; Beadsworth, Mike BJ; McKenna, Mark; Corney, Daniel; Plum, Catherine; Macfarlane, Jamie-Leigh; Matareed, Maisoon; Butt, Sundas; Gupta, Sandipika; et al.
No abstract available